2007
DOI: 10.1039/b704562j
|View full text |Cite
|
Sign up to set email alerts
|

Gas sensors based on nanostructured materials

Abstract: Gas detection is important for controlling industrial and vehicle emissions, household security and environmental monitoring. In recent decades many devices have been developed for detecting CO(2), CO, SO(2), O(2), O(3), H(2), Ar, N(2), NH(3), H(2)O and several organic vapours. However, the low selectivity or the high operation temperatures required when most gas sensors are used have prompted the study of new materials and the new properties that come about from using traditional materials in a nanostructured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
175
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(178 citation statements)
references
References 103 publications
0
175
0
3
Order By: Relevance
“…The synthesis procedure, crystal size and shape, the addition of foreign elements with the role of sensitizers or conductivity modifiers are some of the factors influencing the sensor response [17][18][19][20][21][22][23][24][25].…”
Section: Sensing Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis procedure, crystal size and shape, the addition of foreign elements with the role of sensitizers or conductivity modifiers are some of the factors influencing the sensor response [17][18][19][20][21][22][23][24][25].…”
Section: Sensing Materialsmentioning
confidence: 99%
“…There are already many excellent review articles on this topic in which readers can obtain a complete picture of chemoresistive gas sensors research from various perspectives [8][9][10][11][12][13][14][15][16][17][18][19]. In this brief review, a chronological approach is taken in order to not only examine the past, but also to identify key concepts, new materials and technologies, as well as predict innovative ideas for the future.…”
mentioning
confidence: 99%
“…Iron oxide nanoparticles have shown good sensing capabilities toward hydrocarbon gases, CO and alcohols (Jimenez-Cadena et al, 2007;Han et al, 1996Han et al, , 1999Han et al, , and 2001. The studies by Zhang et al (1996) and Tao et al (1999) showed that -Fe 2 O 3 nanosensors exhibited good sensitivity and selectivity to a range of hydrocarbon gases such as LPG, petrol and C 2 H 2 at 380 °C, but poor sensitivity to H 2 and CO.…”
Section: Gas Sensingmentioning
confidence: 99%
“…In the past decades, many sensor devices have been developed for various gases such as CO, CO 2 , O 2 , O 3 , H 2 , NH 3 and SO 2 , as well as various organic vapors e.g., benzene, methanol, ethanol, amines and isopropanol (Jimenez-Cadena et al 2007). Although semiconducting oxides have been quite useful as gas sensors, the operation at high temperatures often limits their functionality and applications.…”
Section: Gas Sensingmentioning
confidence: 99%
“…Nanomaterials have shown promise for sensing of low concentrations of analyte, due to their high surface area and electronic properties that are affected by the local environment [3][4][5] . In some cases, the particular application and nanomaterial characteristics, permit sensor operation at room temperature, resulting in lower power consumption and increasing sensor suitability for use in portable devices 6 .…”
Section: Introductionmentioning
confidence: 99%